Q methodology as an integrative approach: bridging quantitative and qualitative insights in a mixed methods study on mathematics teachers’ beliefs - Buchholtz, Nils; Vollstedt, Maike (Frontiers in Psychology, 2024)
This study explores the beliefs of pre-service mathematics teachers regarding the teaching and learning of mathematics through a mixed methods approach, combining quantitative Likert-scale surveys and Q methodology, an integrative quantitative and qualitative approach. Utilizing a sample of 33 pre-service teachers, we initially applied Likert-scale surveys to ascertain general trends in belief orientations. Subsequently, the same participants engaged in a Q sort exercise, allowing for a nuanced exploration of individual belief systems by prioritizing the same survey statements within a forced-choice grid. Q methodology analysis identified distinct belief profiles, which were characterized not only by their prioritization of specific educational practices but also by the contextual and subjective interpretations that underpin these preferences. Qualitative interviews further enriched these findings, providing deeper insight into the reasoning behind participants' choices in the Q sort and illustrating how this method illuminates the complex, sometimes contradictory nature of personally held beliefs that traditional Likert-scale approaches may obscure. Our results underscore the utility of combining Q methodology with conventional teacher belief survey techniques to achieve a more holistic understanding of pre-service teachers' beliefs. This approach not only reveals the complexity within individual belief systems but also highlights the potential for mixed methods research to refine the measurement and interpretation of psychological constructs in educational settings.